Household Energy Insecurity and COVID-19 Have Independent and Synergistic Health Effects on Vulnerable Populations - Boateng, Godfred O.; Phipps, Laura M.; Smith, Laura E.; Armah, Frederick A. (Frontiers in Public Health, 2021)
Household energy insecurity (HEINS) is detrimental to the health of the poor and most vulnerable in resource-poor settings. However, this effect amidst the COVID-19 pandemic and the uneven implementation of restrictions can create a synergistic burden of diseases and health risks for the most vulnerable in low- and middle-income countries, exacerbating the health equity gap. Based on existing literature, this paper sets out to develop three key arguments: (1) COVID-19 increases the health risks of energy insecurity; (2) HEINS increases the risk of spreading COVID-19; and (3) the co-occurrence of COVID-19 and HEINS will have compounding health effects. These arguments make context-specific interventions, rather than a generic global health approach without recourse to existing vulnerabilities critical in reducing the spread of COVID-19 and mitigating the effects of energy insecurity. Targeted international efforts aimed at financing and supporting resource security, effective testing, contact tracing, and the equitable distribution of vaccines and personal protective equipment have the potential to ameliorate the synergistic effects of HEINS and COVID-19 in resource-poor countries.